Environmental Impact on Relapse and Motivation Recovery Among Drug Addicts - Asbah Razali, Asbah Razali; Norhidayah Pauzi, Norhidayah Pauzi; Ravindaran A/L Maraya, Ravindaran A/L Maraya; Rosya Izyanie Shamshudeen, Rosya Izyanie Shamshudeen; Razali, Nur Azah; Muhammad Luqman, Muhammad Luqman (2023)
Drug abuse has been proven to be a mental disorder because of the heavy intake of substances usage controlled by the environment. Environmental factors play a significant role in drug addiction and recovery. However, there is a knowledge gap regarding environmental factors contributing to relapse and hinder motivation for recovery among drug addicts in Malaysia. Therefore, the objective of this research is to find out the impact of the environment on drug relapse and motivation recovery in former addicts. For this purpose, a cross-sectional research design was utilized whereby a self-administered questionnaire was randomly distributed among 50 Malaysian drug addicts. Data were analysed through IBM SPSS software version 25.0, and the partial least squares structural equation modelling (PLS-SEM) approach supported by Smart-PLS 3.3 to analyse the research model. The findings of the study indicated that the environment significantly impacts motivation recovery and relapse. Furthermore, the positive environment influences motivation for recovery in former addicts and pushes the addicts to relapse after rehabilitation. The study will provide insights into the environmental factors that contribute to drug addiction and relapse in Malaysia.